C-reactive protein conformations and their association with the IL-1β/IL-6 pathway in ocular inflammatory conditions - Nabaes Jodar, Mercedes S.; Llorenç, Víctor; Figueras-Roca, Marc; Sainz de-la-Maza, Maite; Adán, Alfredo; Molins, Blanca (Frontiers in Immunology, 2025)
IntroductionC-reactive protein (CRP) plays a critical role in the innate immune system and serves as a biomarker for various inflammatory conditions. CRP is a dynamic protein undergoing conformational changes between pentameric (pCRP) and monomeric (mCRP) conformations. pCRP is the well-established systemic marker of inflammation, while mCRP is associated with localized tissue inflammation.MethodsThis study aimed to evaluate systemic levels of pCRP, mCRP, interleukin-6 (IL-6), and interleukin-1β (IL-1β) in patients with a variety of intraocular inflammatory conditions, including diabetic macular edema (DME) and non-infectious uveitis such as Behçet’s disease (BD), Birdshot retinochoroidopathy (BSRC), HLA-B27-associated uveitis, and undifferentiated uveitis (UU).ResultsA total of 77 subjects were included. mCRP levels were significantly elevated in BD, DME, and UU compared to controls (p = 0.014, p = 0.036, and p = 0.031, respectively). The mCRP/pCRP ratio was also significantly higher in DME and UU (p = 0.035 and p = 0.011, respectively). In addition, a strong positive correlation was observed between IL-6 and IL-1β (ρ = 0.638, p <0.0001). No significant differences in serum levels of pCRP, IL-6, or IL-1β were observed among the groups.ConclusionsThese findings suggest that mCRP, rather than pCRP, may be a more specific systemic biomarker for certain intraocular inflammatory conditions. The involvement of the CRP axis and the strong correlation between IL-6 and IL-1β underscore the interaction of these key inflammatory mediators, providing further insight into the targeting of CRP axis for therapeutic purposes.